Utilization of Thiopurine Metabolites and Allopurinol in Pediatric Acute Lymphoblastic Leukemia: Consideration for an Algorithmic Approach. Issue 2 (3rd March 2022) - Mosher, Nichole; Torkildson, Joseph; Golden, Carla; Raphael, Robert; Beach, Barbara; Michlitsch, Jennifer; Feusner, James H.; Agrawal, Anurag K.
Abstract : Persistently elevated absolute neutrophil counts during maintenance for acute lymphoblastic leukemia is a risk factor for relapse and may be related to wild-type thiopurine methyltransferase activity and overly efficient shunting of 6-mercaptopurine to hepatotoxic metabolites (6-methylmercaptopurine nucleotides), leading to low 6-thioguanine nucleotides. 6-mercaptopurine is also metabolized by xanthine oxidase, and therefore allopurinol, an inhibitor of xanthine oxidase, allows for increased 6-thioguanine nucleotides and decreased 6-methylmercaptopurine nucleotide. Here, we report our experience with allopurinol for persistently elevated absolute neutrophil count or hepatotoxicity and suggest an algorithmic approach for checking thiopurine metabolites and initiating allopurinol in acute lymphoblastic leukemia maintenance.